2015
DOI: 10.1589/jpts.27.1865
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a multifactorial fall prevention program on balance, gait, and fear of falling in post-stroke inpatients

Abstract: [Purpose] This study investigated the effects of a multifactorial fall prevention program on balance, gait, and fear of falling in stroke patients. [Subjects] Twenty-five stroke patients were divided randomly into multifactorial fall prevention program group (n=15) and control treadmill group (n=10). [Methods] All interventions were applied for 30 min, five times per week, for five weeks. The fall prevention program included interventions based on the “Step Up to Stop Falls” initiative and educational interven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…Persons with recurrent falls are considered particularly vulnerable and require immediate preventive measures [1]. This finding supports the need for fall prevention, such as a multifactorial fall prevention program [46], in this vulnerable group.…”
Section: Discussionmentioning
confidence: 64%
“…Persons with recurrent falls are considered particularly vulnerable and require immediate preventive measures [1]. This finding supports the need for fall prevention, such as a multifactorial fall prevention program [46], in this vulnerable group.…”
Section: Discussionmentioning
confidence: 64%
“…The 6 min walk test (6MWT) was used as a measure of gait endurance. Subjects performed the 6 min walk test, in which they were instructed to cover as much distance as possible in 6 min 10 ) . Subjects walked around a circuit marked in a 50 m hallway and were allowed to stop and rest if necessary.…”
Section: Methodsmentioning
confidence: 99%
“…Interventions including physical training [ 29 , 31 34 ], cognitive training [ 29 , 35 ], and guided relaxation and imagery therapy [ 36 ] have revealed effects on decreasing FOF among older people under different conditions. A recent study in Korea found that the multifactorial fall prevention program including exercise, education and general physical therapy is effective in improving FOF in post-stroke inpatients [ 37 ]. Although many domains of risk factors for FOF in older adults have been explored, there are still other important aspects that remain under-investigated, such as medical help accessibility which could be imperative for evaluation and prevention of FOF in older adults.…”
Section: Introductionmentioning
confidence: 99%